Answer:
![y(t) = 2e^t -e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zh6wrmmo2bg99n1chiizzwg4ci3u83iz6y.png)
Explanation:
Assuming this complete problem: "In this problem,
y = c1ex + c2e−x
is a two-parameter family of solutions of the second-order DE
y'' − y = 0.
Find a solution of the second-order IVP consisting of this differential equation and the given initial conditions.
y(0) = 1, y'(0)= 3"
Solution to the problem
For this case we have a homogenous, linear differential equation with order 2, and with the general form:
![ay'' +by' +cy=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/9eno7mvbx5c8vcd3fbtt3imfkajoqyxq9h.png)
Where
![a =1, b=0, c=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/otq0rbum8hphjyj6b87iataezd0tq8t686.png)
And we can rewrite the differential equation in terms
like this:
![[e^(rt)]'' -e^(rt)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/2bmz0voug1xk2c6dwafabjhgtxpwnaaqc7.png)
And applying the second derivate we got:
![r^2 e^(rt) -e^(rt)=0](https://img.qammunity.org/2021/formulas/mathematics/high-school/jzsno2rz1yuiyp1v58n1zzh5j9neie0r3s.png)
We can take common factor
and we got:
![e^(rt) (r^2-1) =0](https://img.qammunity.org/2021/formulas/mathematics/high-school/8vm0z2n4pmdk885167nwrllgevvdrtrmb3.png)
And for this case the two only possibel solutions are
![r=1, r=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/r7wlpaaas24i7vb9k9wz6363zdmalx4mbg.png)
And the general solution for this case is given by:
![y = c_1 e^(r_1 t) + c_2 e^(r_2 t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ffmlqqso3d1pbjjui6x852o4h3ynhguimz.png)
Replacing the roots that we found we got:
![y = c_1 e^(t) +c_2 e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ndrx13mp3w3zj7zax5repvxluwttcgps2d.png)
Now we can find the derivates for this last espression
![y' = c_1 e^t -c_2 e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zkxvyxaqvmzewm7jghq6arpox52y206s56.png)
![y'' = c_1 e^t +c_2 e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/tvzy0fjujb1fwljf7mk3pt57kdcze5oxs1.png)
From the initial conditions we have this:
(1)
(2)
If we add equations (1) and (2) we got:
![4 = 2c_1 , c_1 = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/hkgdgf76zx2els3uk6va2ulxxdu1y62hoz.png)
And solving for
we got:
![c_2=3-c_1= 3-2 = 1](https://img.qammunity.org/2021/formulas/mathematics/high-school/5gajvel8fufp816esylvpy26kyzugx0270.png)
So then our general solution is given by:
![y(t) = 2e^t -e^(-t)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zh6wrmmo2bg99n1chiizzwg4ci3u83iz6y.png)